Sensing local energetics to acutely regulate mitophagy in skeletal muscle - Nichenko, Anna S.; Specht, Kalyn S.; Craige, Siobhan M.; Drake, Joshua C. (Frontiers in Cell and Developmental Biology, 2022)
The energetic requirements of skeletal muscle to sustain movement, as during exercise, is met largely by mitochondria, which form an intricate, interconnected reticulum. Maintenance of a healthy mitochondrial reticulum is essential for skeletal muscle function, suggesting quality control pathways are spatially governed. Mitophagy, the process by which damaged and/or dysfunctional regions of the mitochondrial reticulum are removed and degraded, has emerged as an integral part of the molecular response to exercise. Upregulation of mitophagy in response to acute exercise is directly connected to energetic sensing mechanisms through AMPK. In this review, we discuss the connection of mitophagy to muscle energetics and how AMPK may spatially control mitophagy through multiple potential means.